Factors Affecting Online Fitness Platforms Users' Intention to Use - Yiding Liu; Singha Chaveesuk; Bilal Khalid (My University, 2023)
As the standard of living in society continues to rise, more and more individuals are engaging in fitness activities. With the impact of COVID-19 on society, people are gradually realizing the importance of health. Online fitness platforms have been developed to solve some of the problems of the traditional fitness industry. However, if the industry builders of online fitness platforms want to make the platform a good prospect for development, they must understand the user's intention and clarify the factors that influence the user's intention of using online fitness platforms. Due to cost and other reasons, this study was conducted in Wuqing District, Tianjin, and the sample was collected only from this area. The population in the survey area who did not use the online fitness platform was approximately 1,038,153 according to the survey and statistics. This study examined user characteristics, social environment, community influence, publicity and promotion of the platform, perceived usefulness, perceived ease of use, perceived value, and perceived trust, all based on the Technology Acceptance Model (TAM). 385 respondents who had not used an online fitness platform were invited to participate in the online survey for this study. The data were analyzed using descriptive, correlation, and multiple regression analyses. It was concluded that social environment, community influence, perceived ease of use, and perceived value all had a positive impact on the intention to use. The above predictor variables have approximately 82 % explanatory power. This study further enriches the literature of previous related studies, which can enable relevant companies to improve the quality of the platform itself and enhance the positive perception of online fitness platform users.
Keywords: Technology Adoption and User Behaviour; Digital Marketing and Social Media; Impact of Technology on Adolescents